Empowerment-Based Stroke Education to Enhance the Quality of Life (Qol) of Post-Stroke Patients in Kediri City - Christina Dewi Prasetyowati; Giovanni Iga Firmanda (Journal of Ners and Midwifery, 2026)
Stroke can lead to a varied course of disease, ranging from recovery with disability, death, to surviving with recurrent strokes. Post-stroke patients require special attention to improve self-care behaviors or self-care abilities. Stroke empowerment education is an educational approach given to stroke patients with an empowerment focus that centers on the patient.This study aimed to determine the effect of stroke empowerment education on the self-care of post-stroke patients as an effort to prevent recurrent strokes at RSUD Gambiran Kota Kediri. The research design used was a Quasi-Experiment with a pre-post test design with a control group. Sampling was done using accidental sampling technique, resulting in 98 respondents. Data collection on self-care was conducted using the modified version of The Subjective Self-Care Performance Scale questionnaire. The results of the Wilcoxon Signed Ranks Test showed a p-value of 0.000, meaning p < 0.05, thus rejecting H0. This study concluded that there was an effect of stroke empowerment education on improving self-care among post-stroke patients as an effort to prevent recurrent strokes at RSUD Gambiran Kota Kediri. As a recommendation, the results of this study can be continued as an intervention in hospitals to enhance services for post-stroke patients to improve self-care as an effort to prevent recurrent strokes.